A history of Israel from conquest to exile - Davis, John Jefferson; Whitcomb, John C. Dr. (Grand Rapids, MI Baker, 1980)
Includes bibliographical references and indexes.
Originally published in three parts : pt 1 : Conquest and Crisis, 1970; pt 2 : The birth of a Kingdom, 1969; pt 3 : Solomon to the exile, 1971.
Keywords: Bible. O.T. Joshua -- commentaries; Bible. O.T. Judges -- commentaries; Bible. O.T. Samuel -- commentaries; Bible. O.T. Kings -- commentaries